PENGARUH KONSELING AKSEPTOR KB TERHADAP PEMILIHAN ALAT KONTRASEPSI DI WILAYAH KERJA PUSKESMAS PEMURUS DALAM - Yunita, Laurensia; Novita Dewi Iswandari (Midwifery And Complementary Care, 2022)
Background: Indonesia has a policy to control population growth, including through the Family Planning (KB) program. Family planning is an effort made by humans to deliberately regulate pregnancy in the family without going against the laws and morals of Pancasila for the welfare of the family. Through the family planning program, population growth will be controlled so that it can increase the level of health and welfare for families.Quality family planning services are not only related to services in marketing contraceptives, but are also related to providing interpersonal communication/counseling (KIP/K) to acceptors. The importance of the quality of counseling on contraceptive issues by every health worker, especially midwives and doctors, must be increased. Objective: to determine the effect of counseling on the choice of contraceptives in the Pemurus Dalam Health Center working area. Method: This research design uses analytical research with a cross sectional approach. The sample for this research was 30 WUS at Pemurus Dalam Community Health Center. The sampling technique is incidental sampling. Data analysis used chi-square with a questionnaire instrument. Results: The results of data analysis show that there is an influence of providing family planning counseling using ABPK on decision making to use contraception (p=0.000) Conclusion: There is an influence of providing family planning counseling on decision making to use contraception (p=0.000) Keywords: Acceptor, Counseling, Contraception